The association between iron deficiency anemia and febrile seizures - Kalmani, Mallikarjun; Basavaraj, .; Sanikam, Hareesh; K., Pushpalatha; S., Uday Kumar (International Journal of Contemporary Pediatrics, 2021)
Background: Febrile seizures are seizures that occur in children between 6 months and 60 months of age , with body temperature of 38ºC or higher not resulting from Central Nervous System (CNS) infection or any metabolic imbalance without any prior afebrile seizures. Among many risk factors identified for febrile seizures, iron deficiency is hypothesized to be one of the risk factor for occurrence of febrile seizures. Methods: A total of 100 children aged between 6 months to 5 years were included in the present study and were further divided into 2 groups of 50 each, as cases and controls. Control group consisted of age and gender matched children admitted with acute febrile illness without seizures. A detailed history was taken and clinical examination was done in both cases and controls with particular attention to development delay and family history of seizure. Complete haemogram, iron profile and other appropriate investigations were done in both the groups and results were compared. Results: The mean age of onset of febrile seizures was 32 months. There was slightly male predominance, with male: female ratio of 1.27:1. Majority of children with febrile seizures were found to have iron deficiency anemia as opposed to children in control group which was statistically significant. (76% vs 28%), p-value<0.001. All the indices of iron deficiency anemia, like haemoglobin, MCV, MCH, serum iron, serum ferritin were low in febrile seizures group compared to control group. The difference was found to be statistically significant (p-value<0.001). Conclusions: Iron deficiency anemia (IDA) was more frequent among children with febrile seizures. The result suggests that IDA may be a risk factor for febrile seizures. Early detection and timely correction of iron deficiency may be of help for prevention of recurrence of febrile seizures in children of this age group.